Being well in the world: an alternative discourse to mental health and well-being. (2nd January 2019) - Barrow, Giles
ABSTRACT: The author provides a critique of the current campaign promoting well-being and mental health in UK schools. The paper focuses on the unintended consequences of aligning with a medical model of understanding mental health which include concerns about ignoring ecological factors and, to some extent the social construction of individual mental health. The author considers the relevance of Arendt's notion of being at home in the world, (Arendt, 1994), as understood in the context of Biesta's educational commentary, (Biesta, 2017). Finally, the author argues that the current frame of reference for mental health intervention is insufficient in meeting the challenges facing the next generation of students.